Analisis Unit Usaha Badan Usaha Milik Desa (Bum Desa) Kategori Berkembang di Kabupaten Banyuwangi - Nur Anim Jauhariyah; Nurul Inayah; Mahmudah Mahmudah (LP3M STITNU Al Hikmah Mojokerto, 2019)
The aim of the study was to 1) analyze business units at BUM Desa in Banyuwangi District which were in the Developing Category to become the basis for other BUM Desa in Banyuwangi Regency in order to be able to run business units in accordance with local wisdom in the village referring to experiences that had implemented by villages that have BUM Desa that have developed first; 2) Knowing the management strategy in developing business units in BUM Desa which develops in Banyuwangi Regency. This research is a qualitative descriptive study. The results showed that 1) BUM Desa in the developing category has business units that have a Village Market business unit, Department Store, Savings and Loans, Village Canteen, Garbage Transport Services, Hippam, and Online Bank Payment Point (PPOB), Sports Building Management, Clean water / PAM management, PPUB, brick production, all-business cooperative unit, Ijen Home Stay, Ijen Lestari Café, Ijen Tourism Entrance Fee, Village Market (Weekly), Flower Market, Seruni Bathing Pool, Kemping Ground, Hippam, RTH Management / Parking and Management of multi- purpose buildings, Agriculture, Village Markets, Trade, Savings and Loans, Livestock, and Home Industries. 2) The strategy that has been applied to Village- Owned Enterprises (BUMDes) that have been able to develop in their activities, namely specialization, sees village potential and the characteristics of each village that varies. For villages that are close to the tourism sector, the opportunities for welfare of BUMDes can be obtained from tourism development, and strategic rural areas with agricultural potential, then maximized for BUM Desa which is engaged in the agricultural sector.